2009
DOI: 10.1002/car.1095
|View full text |Cite
|
Sign up to set email alerts
|

Girls' and boys' experiences and perceptions of parental discipline and punishment while growing up in China and England

Abstract: This article draws on comparative research involving an exploratory and retrospective survey of 498 students in China and 481 in England and follow‐up interviews, focusing on their experiences of physical punishment and disciplinary behaviour from mothers and fathers ‘while growing up’, including how they felt about their experiences and views concerning what might be perceived as ‘acceptable’ or ‘unacceptable’ punishments. The emphasis is on the Chinese findings, although the English findings are referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…First, it may be explained by the distinct parent gender hierarchy in traditional Chinese society. Specifically, in traditional Chinese families, fathers are the undisputed head of the family having absolute authority over mothers, while mothers are subordinate to fathers (Abbott, Zheng, & Meredith, 1992;Hester, He, & Tian, 2009). Within this social and cultural context, mothers may be more sensitive and vulnerable to the unsatisfying marital relation with their spouse, but not vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…First, it may be explained by the distinct parent gender hierarchy in traditional Chinese society. Specifically, in traditional Chinese families, fathers are the undisputed head of the family having absolute authority over mothers, while mothers are subordinate to fathers (Abbott, Zheng, & Meredith, 1992;Hester, He, & Tian, 2009). Within this social and cultural context, mothers may be more sensitive and vulnerable to the unsatisfying marital relation with their spouse, but not vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Physical punishment should be appropriately used on students who behave badly. It is necessary to exert physical punishment in the Chinese context where light (not severe) physical punishment is more or less acceptable in the Chinese culture (Hester et al, 2009). School rules are common regulations or customs for students to abide by both inside and outside of classroom, which are usually based on culture, courtesy, common sense, personal safety, and are designed to develop social morals and to support effective learning.…”
Section: Interviewsmentioning
confidence: 99%
“…Contrary to Western studies that point to Psychology and Developing societies, 26, 1 (2014): 59-89 the adverse effects of corporal punishment, studies of Chinese families have shown that children who experience corporal punishment do not exhibit externalising problems such as anger, aggression or low academic performance (Steinberg et al, 1992). Rather, children in this culture see strict parental control and use of corporal punishment as acceptable because it is indicative of parental involvement, love and warmth, and is necessary to curb children's wilful disobedience (Chao, 1995;Hester, He and Tian, 2009). Overall, it appears that the larger socio-cultural norms and meanings tend to shape how parents construe and use corporal punishment in their interaction with children.…”
Section: Corporal Punishment As a Methods Of Disciplinementioning
confidence: 99%